Beauvais : Musée Départemental de l'Oise. - Landais, Hubert; Salmon, Marie-José; Musée départemental de l'Oise Beauvais (Beauvais : Musée Départemental de l'Oise, 1981)
Caron, Antoine ; Varin, Quentin ; Batoni, Pompeo ; Bazzani, Giuseppe ; Coccorante, Leonardo ; Diaziani, Gaspare ; Gargiulo, Domenico ; Gaulli, Giovanni Battista ; Giaquinto, Corrado ; Guala, Pietro Francesco ; Maffei, Francesco ; Fieravino, Francesco ; Manetti, Rutilio ; Mazzucheli, Pier Francesco ; Paolini, Pietro ; Ricci, Marco ; Rossi, Nicolo Maria ; Sagrestani, Giovan Camillo ; Serodine, Giovanni ; Spadino, Giovan Paolo ; Strozzi, Bernardo ; Tiarini, Alexandro ; Trevisani, Francesco ; de Boulogne, Valentin ; Van Ost, Jacomo ; Barbault, Jean ; Bertin, Nicolas ; Bourdon, Sebastien ; Brun, Charles Le ; Dughet, Gaspard ; Prince, Jean-Baptiste Le ; Charron, André Charlemagne ; Cabat, Louis ; Chintreuil, Antoine ; Dedreux, Alfred ; Delaplace, Marie Joséphine ; Desboutin, Marcellin ; Dupont, Victor ; Dupré, Léon-Victor ; Huet, Paul ; Ribot, Théodule ; Vollon, Antoine ; Nozal, Alexandre ; Leroy, Paul ; Couture, Thomas ; Delaherche, Auguste ; Serrurier-Bovy, Gustave ; Bellery-Desfontaines, Henri ; Burnes-Jones, Edward ; Menard, René ; Lévy-Dhurmer, Lucien ; Maurin, Charles ; Besnard, Albert ; Dulac, Charles Marie ; Lacoste, Charles ; Martin, Henri ; Devambez, André ; Denis, Maurice ; Desvallières, Georges ; Laurens, Jean-Pierre ; Dupas, Jean ; Despujols, Jean ; Pougheon, Robert ; Leroux, Georges ; Girieud, Pierre ; Boutet-de-Monvel, Bernard ; Lombard, Alfred ; Récipon, Georges ; Blondat, Max ; Gaudissart, Emile ; Valmier, Georges ; Hélion, Jean ; Herbin, Auguste ; Downing, Joe ; de Caro, A.
Frans
boek
Keywords: Beauvais; Frankrijk